2013
DOI: 10.1021/la400782c
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Multiple Equilibria in the Self-Aggregation of Di-n-decyldimethylammonium Chloride/Octaethylene Glycol Monododecyl Ether/Cyclodextrin Ternary Systems

Abstract: The surface tension equations of binary surfactant mixtures (di-n-decyldimethylammonium chloride and octaethylene glycol monododecyl ether) are established by combining the Szyszkowski equation of surfactant solutions, the ideal or nonideal mixing theory, and the phase separation model. For surfactant mixtures, the surface tension at the air-water interface is calculated using nonideal theory due to synergism between the two adsorbed surfactant types. The incorporation of cyclodextrin complexation model to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
(80 reference statements)
0
9
0
Order By: Relevance
“… c Determined from surface tension modelling using single surfactant/cyclodextrin systems in aqueous solution with dilution experiments. d Taken in Leclercq et al., 2013 . …”
Section: Resultsmentioning
confidence: 99%
“… c Determined from surface tension modelling using single surfactant/cyclodextrin systems in aqueous solution with dilution experiments. d Taken in Leclercq et al., 2013 . …”
Section: Resultsmentioning
confidence: 99%
“…For the technical details of combining these with the constitutive equation, the reader is referred to the literature. [40][41][42]…”
Section: Theorymentioning
confidence: 99%
“…Previous work has indicated that double-tailed cationic surfactants have been widely used as fabric softeners, antimicrobials, and antistatic agents [20] in many formulations because of their strong absorbability onto negative surfaces. APG and didecyldimethylammonium chloride (DDAC) mixtures, combining the advantages of pure APG and DDAC, are of particular interest and importance in the development of multi-functional disinfection and washing products [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%